2016
DOI: 10.1038/ncomms12607
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Fzr/Cdh1 for timely activation of the APC/C at the centrosome during mitotic exit

Abstract: A multi-subunit ubiquitin ligase, the anaphase-promoting complex/cyclosome (APC/C), regulates critical cellular processes including the cell cycle. To accomplish its diverse functions, APC/C activity must be precisely regulated in time and space. The interphase APC/C activator Fizzy-related (Fzr or Cdh1) is localized at centrosomes in animal cells. However, neither the mechanism of its localization nor its importance is clear. Here we identify the centrosome component Spd2 as a major partner of Fzr in Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 67 publications
(101 reference statements)
12
54
0
Order By: Relevance
“…, 2012; Sonnen et al. , 2012), which is consistent with a recent study on Drosophila Cdh1/FZR1 (Meghini et al. , 2016).…”
Section: Resultssupporting
confidence: 92%
“…, 2012; Sonnen et al. , 2012), which is consistent with a recent study on Drosophila Cdh1/FZR1 (Meghini et al. , 2016).…”
Section: Resultssupporting
confidence: 92%
“…Because the APC/C Cdh1 recognition motif, the KEN box, is conserved both in Rock1 and Rock2, we next aimed to resolve this apparent paradox. In cancer cells, Rock1 is present in the cytosol and Rock2 both in the nucleus and cytosol (23,24); however, APC is present only in the nucleus (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…APC/C is another ubiquitin E3 ligase complex, which has two activators, Cdc20 and Cdh1. While APC/C Cdc20 plays a role in the early phase of mitosis and in metaphase/anaphase transition, APC/C Cdh1 is activated in the mitotic exit and the early G1 phase to ensure G1 phase progression and to prevent S‐phase entry (van Leuken et al , ; Meghini et al , ). It is also shown that a deletion of Cdh1 delays neurogenesis (van Leuken et al , ; Delgado‐Esteban et al , ).…”
Section: Introductionmentioning
confidence: 99%